Enhancing the efficacy of the 20 m multistage shuttle run test. Issue 3 (23rd February 2005) - Flouris, A D; Metsios, G S; Koutedakis, Y
Abstract : Objective: Maximal oxygen uptake (Vo2max ) of 44 ml kg −1 min −1 is an accepted criterion (Vo2CR ) below which health and fitness for young male adults may be compromised. New algorithms validated for Vo2CR screening using the 20 m multistage shuttle run test (20mMST) were developed. Methods: Vo2max was assessed in 110 males using a stationary gas analyser in a treadmill test (TT) and in 40 of these subjects using a portable gas analyser in the 20mMST. Vo2max predicted from the 20mMST in 70 subjects was used for cross validation. Two equations predicting Vo2max during 20mMST (EQMST ) and TT (EQTT ) were developed. Results: Significant energy cost variance (ECV ) was detected between TT and 20mMST (p<0.001), correlated significantly with subject height, and was a significant predictor of Vo2max differences between TT and 20mMST. The r 2 of EQMST was 0.92 (p<0.001). Predicted Vo2max values from EQMST correlated with directly measured 20mMST Vo2max at r = 0.96 (p<0.001). ANOVA detected no mean difference (p>0.05) between predicted and measured values. Prevalence of low fitness based on Vo2CR was 0.37. McNemar χ 2 indicated significant differences in sensitivity (p<0.001) and specificity (p<0.05) between the original 20mMST equation (EQLÉG ) and EQTT, regarding Vo2CR screening. Cohen's κ demonstrated higher agreement with TT Vo2max for EQTT (p<0.001) than EQLÉG (p<0.05). TT Vo2max correlated with the end result of both EQLÉG and EQTT at r = 0.75 (p<0.001). Unlike EQTT (p>0.05), mean predicted Vo2max from EQLÉG was significantly higher compared to TT Vo2max (p<0.001). Conclusion: These algorithms increase the efficacy of 20mMST to accurately evaluate aspects of health and fitness.